Fermentation of whey and its permeate using a genetically modified strain of Escherichia coli K12 MG1655 to produce 2, 3‐butanediol. Issue 3 (9th August 2021) - Fernández‐Gutiérrez, David; Veillette, Marc; Ávalos Ramirez, Antonio; Giroir‐Fendler, Anne; Faucheux, Nathalie; Heitz, Michèle
Abstract: Whey is generated during cheese manufacturing, and permeate whey is obtained after whey deproteinization. Both effluents contain lactose, which can cause environmental issues if they are released into the environment. The aim of the present study was the valorization of lactose contained in whey and permeate whey via fermentation into 2, 3‐butanediol (2, 3‐BD) with genetically modified strain of Escherichia coli K12 MG1655. Both effluents were first fermented at various dilution ratios with the culture medium M9 (50:50, 75:25, and 100:0, v/v). The fermentation of undiluted effluents produced the highest 2, 3‐BD yield (0.43 g/g lactose) at 72 h. Afterwards, the effects of initial pH, inoculum size and agitation rate on 2, 3‐BD yield in flask fermentation of undiluted effluents were studied. The agitation rates of 50 and 200 rpm resulted in lower 2, 3‐BD yields compared with 100 rpm (67% lower). The effect of aeration (2.5 vvm) on 2, 3‐BD yield was tested in a 2 L bioreactor, where a 2, 3‐BD yield of 0.40 g/g lactose was obtained after 24 h. In the present study, it was demonstrated that both whey and permeate whey can be used to produce 2, 3‐BD, reaching near 80% of the theoretical yield after 24 h of fermentation.